#TITLE_ALTERNATIVE# - PETRUS S. (NIM 12102023); Pembimbing: Dr. Ir. Suseno Kramadibrata, M.Sc., EDWARD
In every mining activity, the effectiveness and efficiency of heavy equipment used are very important to be concerned because it has related with production target and operational cost. PT. INCO as one of the mining companies wants to evaluate the performance of HD785-5 because of the increase of fuel consumption as much as 53,8% from the year 2004 up to 2005 (Source : Production and Cost Report). The evaluation method that has been used in this research is by analyzing the field condition effect-which is focused on grade resistance-and the machinery condition-with special focus on vehicle speed-to fuel consumption. Based on the equation derived from statistical data and data elaboration, it is known that the fuel consumption per hour on HD785-5 increasing with the accumulation of grade resistance experienced by the truck. To overcome the increase of each ton grade resistance on the long haul track, the truck needs more fuel compared to that of short haul. Besides that, the effect of speed to fuel consumption had a different inclination between short haul and long haul track, where on the short haul track, the greater the fuel consumption, the faster speed of the truck. Whereas, on long haul truck it had the opposite result. On the short haul track, the value of the optimum speed that is resulting minimum fuel consumption are approximately 15-17 km/hour and on the long haul track, the optimum speed value is approximately 23-24 km/hour.